Literasi Digital Pustakawan dalam Database Scopus Periode 2010-2020: Studi Bibliometrika - Yupi Royani; Rochani Nani Rahayu (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to see; growth of scientific publications on digital literacy in librarians, core journals of digital literacy scientific publications for librarians, productivity and collaboration of science researchers, digital literacy in librarians, number of publications on digital literacy in librarians by affiliation / institution, number of publications by country, number of publications based on document type, number of publications by subject, 8) map of developments on digital literacy in librarians through keyword clusters. Data obtained from the Scopus database published in the 2010-2020 period. Data analysis using VosViewer software. The results showed that Communication In Computer and Information Science contributed the most articles on digital literacy, then followed by College And Undergraduate, then Reference Services Review journal, the journal with the least amount of Information And Learning Science. The most subjects were Social Sciences with 55.1%, then in the second place were Computer Sciences subjects, namely 21.9%, then the Arts and Humanities subjects were 6.9% followed by Mathematics as much as 5.1%. Meanwhile, the fewest documents were documents on Nursing and Pharmacology, Toxicology and Pharmaceutics with a total percentage of 0.3%, namely 1 document. Trends in knowledge can be seen from the many keywords that are found such as acrl frame work, digital citizenship, digital divide, digital literacy, distance education, distance learning, fake news, higher education, human computer interactive, information literacy, information skills, instructional design, learning. , library instruction, literacy, media literacy, online learning, research, social media. The keywords that are most tied to other networks or other keywords are Information literacy, Digital literacy, Digital literacies, Libraries, Education, Students and Academic libraries.